À qui appartient-il de déterminer les modes d’intervention auprès des personnes intersexuées ? - Bastien Charlebois, Janik (Nouvelles pratiques sociales, 2016)
Les personnes intersex(ué)es sont au coeur de tensions dans l’orientation des pratiques médicales sur leur corps et la détermination de leur « propre bien ». La volonté d’autodétermination relayée par les acteurs sociaux politisés et les critiques qu’ils formulent à l’endroit des médecins se heurtent au déficit de crédibilité que celle-ci leur accorde. En isolant certains des motifs les plus solides du maintien de la primauté médicale sur l’orientation des pratiques, nous relevons les arguments développés par la communauté intersexe pour y répondre. Cette réflexion est menée à partir des perspectives philosophiques de Young sur l’autodétermination et du concept d’injustice épistémique de Fricker.
http://www.erudit.org/fr/revues/nps/2016-v28-n1-nps02990/1039174ar/
Keywords: approches et analyses; autodétermination; corps; cours; discipline; fem1000; histoire et politique; identités LGBTQIA2+; lit4700; militance; médecine; personnes intersexes; point de vue situé; premier cycle; ressource en ligne; sciences; thématiques

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Butch/femme, F2M, pregnant man, tranny-boi: Gender issues in the lesbian community - Herbert, Sandra (Journal of Gay and Lesbian Mental Health, 2010)
The author discusses issues pertaining to transgender women and girls. Women identifying as male or transitioning to becoming male are often ignored in the scientific and lay literature on transgender people. The many newer terms for transgender women and girls are discussed, as well as new ways for transgender girls to express their identities. The importance of family and community supports is discussed, and common issues that young transgender people bring into mental health treatment are elucidated.
Keywords: amériques; discipline; identités LGBTQIA2+; médecine; personnes trans*; ressource en ligne; régions géographiques; santé; sciences; thématiques; états-unis